ON THE SIMULATION OF TIME DERIVATIVE CELLULAR NEURAL NETWORKS - Yavuz, Oguzhan; Polat, S. Nergis Tural; Tavsanoglu, Vedat (EUROPEAN ASSOC SIGNAL SPEECH & IMAGE PROCESSING-EURASIP, 2010)
In this paper our previously proposed TDCNN simulation formulation is rewritten in vector-matrix form and thus a matrix condition for the empirical time constraint given in [1] is derived. The sinusoidal simulation results for bandpass filter example are presented.
Keywords: Engineering